REDESIGN OF THE WARUNG PEJALAN SURAKARTA LOGO TO STRENGTHEN BRAND AWARENESS - Ardian Safitri, Mike; Prameswari, Nadia Sigi (LPPM Univ. Ibn Khaldun Bogor, 2025)
A logo redesign is a strategic step in strengthening brand awareness for a business. Warung Pejalan, a coffee shop and literacy community based in Surakarta, faces challenges in establishing a consistent and communicative visual identity. This study aims to redesign the logo of Warung Pejalan as an effort to enhance a more relevant and adaptive visual identity, particularly targeted at young audiences and the local community. The method used is a qualitative approach through observation, interviews, literature review, and documentation, analyzed using SWOT techniques. The final output consists of a new logo design and its implementation across primary media, accompanied by a visual perception survey of potential consumers. It is expected that the result will provide a visual solution that strengthens the brand’s image and positioning.